Assessment of the Risk of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Reinfection in an Intense Reexposure Setting. (14th December 2020) - Abu-Raddad, Laith J; Chemaitelly, Hiam; Malek, Joel A; Ahmed, Ayeda A; Mohamoud, Yasmin A; Younuskunju, Shameem; Ayoub, Houssein H; Al Kanaani, Zaina; Al Khal, Abdullatif; Al Kuwari, Einas; Butt, Adeel A; Coyle, Peter; et al.
Abstract: Background: Risk of reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is unknown. We assessed the risk and incidence rate of documented SARS-CoV-2 reinfection in a cohort of laboratory-confirmed cases in Qatar. Methods: All SARS-CoV-2 laboratory-confirmed cases with at least 1 polymerase chain reaction–positive swab that was ≥45 days after a first positive swab were individually investigated for evidence of reinfection. Viral genome sequencing of the paired first positive and reinfection viral specimens was conducted to confirm reinfection. Results: Out of 133 266 laboratory-confirmed SARS-CoV-2 cases, 243 persons (0.18%) had at least 1 subsequent positive swab ≥45 days after the first positive swab. Of these, 54 cases (22.2%) had strong or good evidence for reinfection. Median time between the first swab and reinfection swab was 64.5 days (range, 45–129). Twenty-three of the 54 cases (42.6%) were diagnosed at a health facility, suggesting presence of symptoms, while 31 (57.4%) were identified incidentally through random testing campaigns/surveys or contact tracing. Only 1 person was hospitalized at the time of reinfection but was discharged the next day. No deaths were recorded. Viral genome sequencing confirmed 4 reinfections of 12 cases with available genetic evidence. Reinfection risk was estimated at 0.02% (95% confidence interval [CI], .01%–.02%), and reinfection incidence rate was 0.36 (95% CI, .28–.47) per 10 000 person-weeks. Conclusions: SARS-CoV-2 reinfection can occur but is a rare phenomenon suggestive of protective immunity against reinfection that lasts for at least a few months post primary infection. Abstract : In a cohort of 133 266 laboratory-confirmed cases, the risk of severe acute respiratory syndrome coronavirus 2 reinfection was 0.02%, and the incidence rate of reinfection was 0.36 per 10 000 person-weeks. Reinfection rarely occurs, indicating protective immunity for at least a few months post primary infection.